Application of stable isotope tools for evaluating natural and stimulated biodegradation of organic pollutants in field studies. (October 2016) - Fischer, Anko; Manefield, Mike; Bombach, Petra
Graphical abstract: Highlights: CSIA enables assessment of biodegradation of low-molecular weight organic pollutants. In situ -microcosms using fatty-/amino acid SIP allows detection of pollutant assimilation. Laboratory microcosms using 13 C-labelled pollutants enable quantification of pollutant mineralisation. DNA-/RNA-SIP facilitates identification of microorganisms responsible for pollutant biodegradation. Multiple-line-of-evidence-approaches encompassing stable isotope techniques should be the backbone of evaluation of pollutant biodegradation. Abstract : Stable isotope tools are increasingly applied for in-depth evaluation of biodegradation of organic pollutants at contaminated field sites. They can be divided into three methods i) determination of changes in natural abundance of stable isotopes using compound-specific stable isotope analysis (CSIA), ii) detection of incorporation of stable-isotope label from a stable-isotope labelled target compound into degradation and/or mineralisation products and iii) determination of stable-isotope label incorporation into biomarkers using stable isotope probing (SIP). Stable isotope tools have been applied as key monitoring tools for multiple-line-of-evidence-approaches (MLEA) for sensitive evaluation of pollutant biodegradation. This review highlights the application of CSIA, SIP and MLEA including stable isotope tools for assessing natural and stimulated biodegradation of organic pollutants in field studies dealing with soil and groundwater contaminations.